‘Societal Security’ and Iceland - Bailes, Alyson J.K., 1949-; Þröstur Freyr Gylfason 1979- (2008)
Almenn grein The doctrine of “societal security” is applied in some other Nordic countries to coordinate policy and action on all (non-military) internal emergencies, terrorist, man-made or natural. It stresses a society-based rather than sovereignty-based outlook and should empower economic and social actors to help build their own security. An elite opinion survey in Iceland, spring 2008, suggests that many Icelanders would welcome such an approach as a way to update, balance, and widen ownership of national security policies. Many think it would help avoid any departmental monopoly and enhance the head of government’s coordinating role. The concept would however need major adaptation to Iceland’s threat profile - where natural disasters and economic interdependence loom larger - and in order to preserve independent non-state competences such as the volunteer rescue force. An Icelandic move in this direction could facilitate cooperation with the Nordic group but also EU and other institutions. Nevertheless, Iceland is only mid-way through a major policy adjustment following US troop withdrawals in 2006, and some opinions on security remain widely polarized. Nearterm domestic developments are subject to many uncertainties but, as the opinion survey suggests, Icelandic policies will surely converge more with their neighbours’ over time.